Uso do aplicativo Slice Fractions como objeto de aprendizagem móvel para matemática: relato de experiência de uma aula sobre frações - Melo, Elvis Medeiros de (2018)
This paper presents the experience report of a fraction class with a fifth grade class in a Natal, Rio Grande do Norte. The objective of the activity was to reinforce concepts about fraction seen previously, with the activities of the educational app Slice Fractions. The use of the Bring Your Own Device (BYOD) played an important role, since students spend a lot of time with their smartphones. We applied a questionnaire to know the students' perception about the practice. 90% of the students considered the practice to be significant, reinforcing that activities based on educational software, such as education-oriented apps potentiate the learning